Semiotics Of French Crop Hairstyles Lecturer At Islamic University - Nasrullah, Nasruddin (Jurnal Khabar: Komunikasi dan Penyiaran Islam, 2023)
One of the hairstyles that is currently trending is the French crop hairstyle. Even though everyone has the right to choose any hairstyle, what is interesting in this article is that an academic chose a French crop hairstyle that was different from academics in general. The aim of this research is to find out the hidden meaning that Prof. wants to convey. Iswandi Syahputra, through the French Crop hairstyle that he uses using Roland Barthes' semiotic analysis. The research method used in this research is field research, namely research carried out by participating directly at the research location to explore and obtain information related to the meaning contained in Iswandi Syahputra. The collected data will be analyzed semiotically using interpretive techniques. The results of this research are that there is a religious meaning, namely that he wears a French Crop hairstyle as a form of obedience to the Prophet Muhammad. and there is also an ideological meaning, namely locally based with a global perspective, he wants even though we are only local people, we must have broad insight.